Formation Of Active Citizenship Competences In Children With Hearing Problems (Pedagogical Cluster-Journal of Pedagogical Developments, 2023)
This article describes the current issues of active citizenship formation in children with hearing problems, the tasks set in the process of forming legal education in educational activities.